The current debate on border(s) applied to the Iberian case: elements of de-bordering and re-bordering between Spain and Portugal in the 21st Century - Lois González, Rubén Camilo; Escudero Gómez, Luis Alfonso; Gusman, Inês (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2019)
Since the last decades of the 20th century, the narrative of a world without borders, where territorial relations are no longer determined by States, has been gaining strength among academics and decision-makers. Transnational cooperation projects such as the European Union (EU) seem to demonstrate that borders no longer represent economic, political and social discontinuities. These new scenarios have opened a new phase in the relations between the territories of Spain and Portugal and overcome the historical separation. This is a rapprochement reflected in the creation of cross-border cooperation structures and in the decades of constantly growing economic relations between both countries, although the process was slowed by the economic crisis beginning in 2008. In this paper, the focus is the evolution of these relationships and also an analysis of the effectiveness of cooperation as an adequate means for overcoming the effects of the crisis. Since the crisis ended, cross-border relations between Portugal and Spain have regained their vigour, especially at the local and regional levels. Thus, thanks to cultural, social and economic complementarities, cooperation can overcome the limits of States and be conceived as an effective instrument for territorial development.